2017
DOI: 10.1002/mrd.22838
|View full text |Cite
|
Sign up to set email alerts
|

Controlling lactation oestrus: The final frontier for breeding herd management

Abstract: Lactation anoestrus limits the flexibility of modern pig production systems such that any increase in lactation length reduces farrowing frequency, and thus profit. This review focuses on post-partum development of the sow's reproductive system, the physiology of lactation anoestrus and how it can be overcome, as well as the fertility of sows mated while lactating. The propensity for sows to ovulate spontaneously while lactating is high (24-31%), and a high proportion of sows will ovulate rapidly and synchrono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 88 publications
(153 reference statements)
0
7
0
Order By: Relevance
“…Based on recent Dutch and Australian studies van Wettere et al. () concluded that “the capacity of modern sows, of various genotypes, to spontaneously ovulate during a 21‐ to 28‐day lactation period is clearly high,” although most likely, spontaneous ovulations will take place more towards the end of a 28‐day lactation.…”
Section: Selection For Shorter Weaning‐to‐oestrus Interval: Consequenmentioning
confidence: 99%
“…Based on recent Dutch and Australian studies van Wettere et al. () concluded that “the capacity of modern sows, of various genotypes, to spontaneously ovulate during a 21‐ to 28‐day lactation period is clearly high,” although most likely, spontaneous ovulations will take place more towards the end of a 28‐day lactation.…”
Section: Selection For Shorter Weaning‐to‐oestrus Interval: Consequenmentioning
confidence: 99%
“…There are two main reasons why IS has been examined over the years. The first reason is to induce estrus in lactation, allowing for mating in lactation, which presents an opportunity to uncouple estrus cycling from weaning, therefore extending the weaning age (e.g., to 5-8 weeks) without decreasing the number of litters produced per sow per year ( [146,147]; for reviews). Second, IS has also been studied as a strategy to promote supplementary (e.g., creep) feed intake in piglets during lactation.…”
Section: Intermittent Suckling To Promote Gradual Weaningmentioning
confidence: 99%
“…Reducing the suckling stimulus in a controlled manner (i.e., not relying on sows to regulate nursing frequency) by subjecting litters to interrupted suckling techniques such as IS has been used on its own or in combination with the techniques mentioned above to increase gonadotrophin release and can result in a 100% occurrence of estrus in lactation. However, the results are still highly variable, most likely due to factors such as sow parity, metabolism, litter suckling intensity, seasonal effects, and litter creep feed intake [147,150].…”
Section: Intermittent Suckling and Extended Lactation: Effects On Lit...mentioning
confidence: 99%
“…Using sows as nurse sows increases the likelihood that they exhibit a lactational oestrus caused by changes in litter dynamics during lactation. Lactational oestrus can be induced by intermittent suckling (Langendijk et al, 2009; Soede et al, 2012; van Wettere et al, 2017) or by the transfer of a sow to a new pen (van Wettere et al, 2017). When nurse sows are transferred to a new pen, there is typically a period of time when there is no nursing activity.…”
Section: Potential Risks When Increasing the Length Of The Lactation ...mentioning
confidence: 99%